SURVEY OF MEDICINAL PLANTS FOUND IN MUZAFFARPUR, BIHAR - SUMAN SOURABH (International Journal of Multidisciplinary Research and Studies, 2020)
Since the beginning of healthcare, people have taken advantage of the healing properties of various plants. There have been investigations conducted all around the world to determine their usefulness, and some of the findings have resulted in the development of medications that are derived from plants. The annual market value of medical plant products is estimated to be over one hundred billion dollars worldwide. The function, contributions, and usefulness of medicinal plants in the fight against diseases of public health relevance are the topics of discussion in this paper. A particular emphasis is placed on the many strategic methods that are now being used to prevent disease. The ’high-risk’ strategy is contrasted with the ’whole population’ strategy in this discussion. This article highlights the efficacy of the common-factor approach as a technique of involving other health promoters in the dissemination of the values associated with medicinal plants. The five fundamental tenets of the Primary Health Care (PHC) method are used as a framework for conducting additional research on the role that medicinal plants play in the avoidance of prevalent diseases. Medicinal plants provide essential functions in disease prevention, and the promotion and utilization of these plants is compatible with every prevention strategy currently in existence. during the planning and execution of these strategies, concerted efforts are required to correctly identify, acknowledge, and place medicinal plants in their appropriate contexts. In the field of medicinal plants, these different techniques present a number of interesting and new perspectives. In order to better strategize the future place and function that medicinal plants will play in disease prevention, some recommendations have been offered.